Моделювання перспективного планування бюджету промислового міста (на прикладі м. Донецька) - Мадих, А.А.; Мазур, Ю.О.; Охтень, О.О. (Економіка промисловості, 2014)
Запропоновано вдосконалений інформаційно-аналітичний комплекс перспективного планування дохідної частини бюджету промисло- вого міста, призначений для наукової та інформаційної підтримки прийняття відповідних рішень. Він складається з моделей середньострокового планування доходів бюджету м. Донецька. Даний комплекс є науковим інструментом, який дозволяє аналізувати соціально-економічний розвиток міста та його бюджет у ретроспективі. Предложен усовершенствованный информационно-аналитический комплекс перспективного планирования доходной части бюджета промышленного города, предназначенный для научной и информационной поддержки принятия соответствующих решений. Он состоит из моделей среднесрочного планирования доходов бюджета г. Донецка. Данный комплекс является научным инструментом, который позволяет анализировать социально-экономическое развитие промышленного города и его бюджет в ретроспективе. It is considered that industrial development in Ukrainian economy depends on effective tax regulation. It manifests itself in the creation of conditions for sustainable economic growth based on the tax system convenient for taxpayers. Perspective planning of the city's budget, its revenue and expenditure parts, is one of the important activities of local authorities that are stated in the Budget Code of Ukraine. High-quality execution of this important function requires using modern scientific and analytical tools which will improve the quality of management of the socio-economic development of the industrial city.This article proposes an improved information-analytical complex for long-term planning of the industrial city budget intended for scientific and informational support for decision-making. It consists of models for medium-term forecasting of Donetsk city budget revenues. This complex is a research tool that allows analyzing the socio-economic development of the industrial city as well as its budget in retrospect, estimating planned tax revenues of the industrial city in the medium term (next 3 years) with a high degree of accuracy and adequacy to the actual real socio-economic processes. The complex tax models of medium-term economic development of the industrial city are proposed. These models include the interactive models predicting the land tax, land rent, personal income tax, single tax, and general tax revenues.According to the forecasts of medium-term planning and provided that in 2014-2016 Ukraine's GDP growth equals 2% annually and the real rate of price growth (GDP deflator) is 9% annually, tax revenues will grow from UAH 2.178 mln in 2012 to UAH 2.465 mln in 2016. This change will occur mainly due to the expected growth in personal income tax in the city budget from UAH 1.468 mln in 2012 to UAH 1.738 mln in 2016. Actualization of the complex allows getting updated forecasts of economic development and industrial city budget revenues for the next three fiscal periods. The resulting forecast can be used for scientific substantiation of administrative decisions of city authorities and improving the quality of budget planning and forecasting.